The Strategic Use of Service Design for Leaders in Service Organizations - Gloppen, Judith (FormAkademisk, 2011)
There is a growing interest among scholars, practitioners and organizations as to how design may benefit management, particularly when this happens in a service context. In this exploratory qualitative study, I investigate such a multi-disciplinary intersection with the aim of better understanding how service design may be of value for leaders in service organizations on a strategic level. The research draws on a service design approach called AT-ONE. Addressed are ways that the strategic use of service design may influence attitudes and transformation in service organizations. The study presents views from the designers, implementers and users of this approach, supported by participant observation and interviews. This was done through in-depth qualitative interviews with the AT-ONE project members and designer, with the service design professional company involved, and leaders from the businesses participating in the project and workshop sessions. These were observed by the researcher. Drawing on the findings of this exploratory study, some implications for the field of service design management at the corporate level are offered.